Testing of biomatrix construct - Leong, Heng Weng. (2008)
A complete tear of the anterior cruciate ligament (ACL) is one of the most frequent and severe injuries of the knee. An ACL-deficient knee is unstable, often leading to injuries of other soft tissues in and around the knee. Because the substance of the ACL has limited healing capabilities, tears of this tissue often require surgical reconstruction. Since 19060 when silk was used as a replacement for damaged knee ligament, many autograft tissues and synthetic materials have attempted to mimin the properties of the natral ligament. The objective of ths project is to investigate the mechanical propertes of various tissue-engineered Biomatrix constructs from Bio Nova International Pte. Ltd. Tensile test on four different types of Biomatrix constructs were investigated. There are namely 4mm single strand, 6mm single strand, 4mm braided and 6m braided. The results will be used to justify the suitability of the Biomatrix constructs as a replacement for torn ACL. From the tests conducted in this project, it has been shown that the Biomatrix constructs were unsuitable to be used as a replacement from torn ligaments.